Are working practices of lung cancer nurse specialists associated with variation in peoples' receipt of anticancer therapy?. (September 2018) - Stewart, Iain; Khakwani, Aamir; Hubbard, Richard B.; Beckett, Paul; Borthwick, Diana; Tod, Angela; Leary, Alison; Tata, Laila J.
Highlights: Early nurse specialist contact is associated with greater receipt of therapy. Receipt of surgery is less likely where nurse specialists have large caseloads. Therapy receipt is more likely if key nursing interventions are routinely provided. Managing nurse specialists' workload could address disparities in therapy uptake. Abstract: Objectives: Treatment choices for people with lung cancer may be influenced by contact and engagement with lung cancer nurse specialists (LCNSs). We investigated how service factors, LCNS workload, and LCNS working practices may influence the receipt of anticancer treatment. Materials and methods: English National Lung Cancer Audit data and inpatient Hospital Episode Statistics for 109, 079 people with lung cancer surviving 30 days from diagnosis were linked along with LCNS workforce census data and a bespoke nationwide LCNS survey. Multinomial logistic regression was used to determine adjusted relative risk ratios (RRRs) for receipt of anticancer therapies associated with LCNS assessment, LCNS workforce composition, caseload, LCNS reported working practices, treatment facilities at the patients' attending hospitals, and the size of the lung cancer service. Results: Assessment by an LCNS was the strongest independent predictor for receipt of anticancer therapy, with early LCNS assessments being particularly associated with greater receipt of surgery (RRR 1.85, 95%CI 1.63–2.11). For people we considered clinically suitable for surgery, receipt was 55%. Large LCNS caseloads were associated with decreased receipt of surgery among suitable patients (RRR 0.71, 95%CI 0.51–0.97) for caseloads >250 compared to ≤150. Reported LCNS working practices were associated with receipt of surgery, particularly provision of psychological support (RRR 1.60, 95%CI 1.02–2.51) and social support (RRR 1.56, 95%CI 1.07–2.28). Conclusion: LCNS assessment, workload, and working practices are associated with the likelihood of patients receiving anticancer therapy. Enabling and supporting LCNSs to undertake key case management interventions offers an opportunity to improve treatment uptake and reduce the apparent gap in receipt of surgery for those suitable.